(untitled) (Biological Sciences - PJSIR, 2025)
Zinc phosphate (ZnP) has many implementations in different areas. Nanoparticle materials synthesis utilizing plant extracts is an alternative to classic physical and chemical methods. The biological synthesis of nanoparticles is of significant importance due to its simplicity, eco-friendliness and extensive antimicrobial activity.